2015
DOI: 10.1113/jphysiol.2014.273839
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory and excitatory neuromodulation by hydrogen peroxide: translating energetics to information

Abstract: Historically, brain neurochemicals have been broadly classified as energetic or informational. However, increasing evidence implicates metabolic substrates and byproducts as signalling agents, which blurs the boundary between energy and information, and suggests the introduction of a new category for 'translational' substances that convey changes in energy state to information. One intriguing example is hydrogen peroxide (H 2 O 2 ), which is a small, readily diffusible molecule. Produced during mitochondrial r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
37
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 119 publications
(360 reference statements)
1
37
0
Order By: Relevance
“…A variety of heteroreceptors and the D2 autoreceptor can also regulate Ca 2+ currents in DA axons [178] (see Section 1.4.1). The specific Ca 2+ channels required for somatodendritic DA release remain uncertain [179], given that the release process can be triggered in very low extracellular Ca 2+ concentrations [180]; contributing factors, including intracellular Ca 2+ stores [181], are discussed elsewhere [182]. …”
Section: Regulation Of Dopamine Releasementioning
confidence: 99%
See 2 more Smart Citations
“…A variety of heteroreceptors and the D2 autoreceptor can also regulate Ca 2+ currents in DA axons [178] (see Section 1.4.1). The specific Ca 2+ channels required for somatodendritic DA release remain uncertain [179], given that the release process can be triggered in very low extracellular Ca 2+ concentrations [180]; contributing factors, including intracellular Ca 2+ stores [181], are discussed elsewhere [182]. …”
Section: Regulation Of Dopamine Releasementioning
confidence: 99%
“…The effects of ionotropic glutamate-receptor activation on DA release are most likely indirect given that DA terminals lack these receptors [258,259]. Studies by Margaret Rice’s group suggest that glutamatergic regulation of DA release in CPu is indirect and mediated by AMPA receptors on striatal medium spiny neurons, as reviewed elsewhere [182,260]. Briefly, AMPA receptor-dependent activation of striatal spiny neurons enhances mitochondrial H 2 O 2 generation [261].…”
Section: Regulation Of Dopamine Releasementioning
confidence: 99%
See 1 more Smart Citation
“…[29] Even at lower concentrations,h ydrogen peroxide is recognized to alter cell signaling, [30] particularly in sensitive cells like neurons. [31] These effects are highly dependent on the specific conditions and identity of the cells in question. [32] The diversity of effects over ar ange of concentrations makes it difficultt op redict what might happen upon addition of hydrogenp eroxide to any given cell line.…”
mentioning
confidence: 99%
“…The authors conclude by highlighting the need for more research on this topic to better define how the brain expends energy on non-signalling tasks. Lee and colleagues from New York University School of Medicine examine the emerging idea that ROS lie at the hub of a number of signalling pathways in the brain (Lee et al 2015). The authors focus on the role of hydrogen peroxide (H 2 O 2 ) which the Rice lab has shown to be an endogenous modulator of dopamine release in the striatum (Chen et al 2001).…”
mentioning
confidence: 99%